Trace metal dynamic speciation studied by scanned stripping chronopotentiometry (SSCP) - Domingos, R. F. (2013)
Abstract. The ability of scanned stripping chronopotentiometry (SSCP) to obtain dynamic information for metal complexation with heterogeneous colloidal ligands was evaluated by measurements of lead(II) and cadmium(II) complexation by humic and fulvic acids extracted from an ombrotrophic peat bog. Average stability constants were calculated, using a first order chemical heterogeneity approach, and compared with those obtained by an ion selective electrode (ISE). SSCP average stability constants were overestimated in comparison to those obtained by the ISE, which suggests that the first order heterogeneity approach did not fully account for the ligand heterogeneity. However, the comparison of the stability constants obtained from the two SSCP signals (the shift of the half-wave potential and the decrease of transition time) provides information about the dynamic nature of the metal complexes formed with the humic matter. These results were in reasonable agreement with the theoretical predictions of the dynamic theory for colloidal systems.